Organizational Agility and Job Engagement among Staff Nurses - Fawzia Badran; Azza Khaled (Evidence-Based Nursing Research)
Context: Agility is one of the adjustments organizations must make in a tumultuous environment. Organizational agility is a collection of concepts that aims to maximize both tangible and intangible resources while continuously improving the organization as a whole. It has a great impact on job engagement among nurses.